The maturity premium - Chaderina, Maria; Weiss, Patrick; Zechner, Josef (Journal of Financial Economics, 2022)
We show that firms with longer debt maturities earn risk premia not explained by unconditional factors. Embedding dynamic capital structure choices in an asset-pricing framework where the market price of risk evolves with the business cycle, we find that firms with long-term debt exhibit more countercyclical leverage. The induced covariance between betas and the market price of risk generates a maturity premium similar in size to our empirical estimate of 0.21% per month. We also provide direct evidence for the model mechanism and confirm that the maturity premium is consistent with observed leverage dynamics of long- and short-maturity firms.